Nursing of a premature infant with respiratory distress syndrome treated with comprehensive therapy and ethnomedicine external application (常规干预联合民族医外治疗法治疗1例呼吸窘迫综合征早产儿的护理体会) - LONG Liling (龙荔玲) (中西医结合护理)
To summarize the nursing points of a premature infant with respiratory distress syndrome (RDS) treated with comprehensive therapy and ethnomedicine external application. Key points of nursing included medication care of pulmonary surfactant, body position management, touching combined with acupoint therapy, Traditional Chinese Medicine bath, five-element music therapy and feeding care. (本文总结常规干预联合民族医外治疗法治疗1例呼吸窘迫综合征早产儿的护理经验。护理要点包括肺表面活性物质(PS)给药护理、体位管理、抚触联合点穴疗法、中药泡浴、五行音乐疗法、喂养调护。)